Study of Sociological Aspects of Traditional Medicine in Inland Communities in West Java, Indonesia - Karmilah, Karmilah (HM Publisher, 2024)
Traditional medicine is a form of health service that has existed for a long time in Indonesia. Traditional medicine is still used by some people, especially people in rural areas. This research aims to examine the sociological aspects of traditional medicine in rural communities in West Java, Indonesia. This research uses a qualitative method with a case study approach. The research informants consisted of 10 people who were traditional medicine practitioners and people who used traditional medicine. Data was collected through in-depth interviews and observations. The results of the research show that traditional medicine in rural communities in West Java, Indonesia, has an important role in people's lives. Traditional medicine is used to treat various diseases, both physical and non-physical. Traditional medicine is also used to maintain health and improve people's quality of life. The discussion shows that traditional medicine has important social values for the people of inland West Java, Indonesia. These social values include the value of togetherness, the value of local wisdom, and the value of solidarity. Traditional medicine also plays a role in strengthening the cultural identity of the people of inland West Java, Indonesia. The research conclusion shows that traditional medicine is an inseparable part of the lives of the people in the interior of West Java, Indonesia. Traditional medicine has an important role in social, cultural, and public health aspects.